2018
DOI: 10.1021/acsomega.8b00182
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired General Interface Modification Method and Its Application in Polymer Reinforcement and as a Flame Retardant

Abstract: Inspired by the remarkable adhesion of mussels, the mimicking of natural adhesive molecules has been widely used for surface modification. In the present study, an economical and easily available biomimic material named as tannic acid–Fe 3+ (TA–Fe 3+ ) was first directly used as a surface modifier, carbonization agent, smoke inhibitor, and flame-retardant synergist. Compared with the flame-retardant magnesium hydroxide (Mg(OH) 2 ), TA–Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…However, polymer composites of metal hydroxides can exhibit poor adhesion to surfaces. Taking inspiration from mussels (in which catechol and amino groups are important for adhesion), it was recently shown that this problem could be addressed in a synergistic manner, by the incorporation of tannic acid-Fe(III) complexes and Mg(OH) 2 into a polyamide-6 (PA 6, an industrially-important polymer) matrix [ 19 ]. Tannic acid-Fe complexes can be used to coat materials on the surface because of their strong chelating properties and were used in this study to stabilize polymer–hydroxide composites through non-covalent interactions.…”
Section: Bio-based Fr Materialsmentioning
confidence: 99%
“…However, polymer composites of metal hydroxides can exhibit poor adhesion to surfaces. Taking inspiration from mussels (in which catechol and amino groups are important for adhesion), it was recently shown that this problem could be addressed in a synergistic manner, by the incorporation of tannic acid-Fe(III) complexes and Mg(OH) 2 into a polyamide-6 (PA 6, an industrially-important polymer) matrix [ 19 ]. Tannic acid-Fe complexes can be used to coat materials on the surface because of their strong chelating properties and were used in this study to stabilize polymer–hydroxide composites through non-covalent interactions.…”
Section: Bio-based Fr Materialsmentioning
confidence: 99%
“…Tannic acid (TA) acts mainly in the solid phase as a char former due to its polyphenolic structure, shown in Figure a. It is an inherently intumescent compound, possessing the three characteristics required for that function: it is an acid source (containing many ester groups), a good carbon source and char former (composed mainly of benzene rings), and a blowing agent (releasing CO 2 during decomposition). , Researchers have used tannic acid, either alone or in combination with other additives, to reduce the flammability of epoxy aerogels, , PLA aerogels, , PLA resin, PA6, , polyesters and polyester/ABS blends, and polyolefins such as LDPE and PS . Another naturally occurring polyphenolic compound, lignin, has been used in ABS to reduce its flammability; ,, tannic acid has a similar structure and char-forming capacity as lignin, with the advantage of having a greater structural and compositional regularity, making it a promising candidate for use in ABS.…”
Section: Resultsmentioning
confidence: 99%
“…Magnesium hydroxide (MH) and alumina trihydrate (ATH) act mainly in the solid phase as "heat sinks", lowering the burning material's temperature as they endothermically decompose and release water. A drawback related to their use is that these additives are normally needed in large quantities to be effective, which often diminishes the polymer's mechanical properties; 26 this can potentially be mitigated using them in lower quantities in combination with other FRs. Wang et al 26 used MH together with TA−iron complexes in PA6, improving both the flame resistance and the mechanical properties of the polymer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations